2015
DOI: 10.1007/s40618-015-0361-0
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective observational analysis of non-irradiated non-functioning pituitary adenomas

Abstract: Based on the given lack of approved medical treatment and the possible risks of surgical intervention in presence of significant comorbidities, our study proposes a conservative approach with a careful follow-up in patients with NFPAs without visual or neurological abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Previous longitudinal cohort studies have been limited by their small sample sizes and heterogeneity, with only 2 studies including more than 50 participants. 2,[4][5][6]8,10,12,14,15,[18][19][20] In addition, some studies have reported neither endocrine dysfunction nor the definition of an increase in tumor size. 2,4,8,18,20 Even the Endocrine Society's guidelines were dependent on the experience of a task force of experts.…”
mentioning
confidence: 99%
“…Previous longitudinal cohort studies have been limited by their small sample sizes and heterogeneity, with only 2 studies including more than 50 participants. 2,[4][5][6]8,10,12,14,15,[18][19][20] In addition, some studies have reported neither endocrine dysfunction nor the definition of an increase in tumor size. 2,4,8,18,20 Even the Endocrine Society's guidelines were dependent on the experience of a task force of experts.…”
mentioning
confidence: 99%
“…We can assume that only a minority of nonfunctioning PAs exhibit considerable growth and become clinically relevant, while the majority remain stable or show extremely slow growth velocity [11]. Many previous studies have also proposed a conservative approach with careful follow-ups in patients with PAs without visual or neurological abnormalities [1,6,13,18]. So, the ‘wait-and-see’ policy might seem reasonable for PAs without symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Pituitary adenomas (PAs) are not usually associated with clinical syndromes related to hormone excess and may be discovered occasionally, when they are not hormonally active [13]. So, they usually escape early diagnosis and are mainly discovered when they exert mass effects on surrounding tissues leading to visual impairments, headache and hypopituitarism [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because only 25% of the nonfunctioning macroadenomas increase in size significantly during follow-up[ 2 9 ] after the first surgery, we opted for clinical follow-up for this patient. Moreover, it is known that the extent of tumor removal has no impact at mortality in these patients.…”
Section: Discussionmentioning
confidence: 99%